2008
DOI: 10.1109/tmtt.2008.2007359
|View full text |Cite
|
Sign up to set email alerts
|

Low Insertion-Loss Single-Pole–Double-Throw Reduced-Size Quarter-Wavelength HEMT Bandpass Filter Integrated Switches

Abstract: This paper proposes a circuit topology which reduces the chip size of single-pole-double-throw (SPDT) quarter-wavelength bandpass filter-integrated switches (FIS). A 40-GHz mHEMT MMIC SPDT switch has been implemented and demonstrates a measured insertion loss lower than 1 dB and an isolation better than 30 dB. Another 50-GHz pHEMT MMIC SPDT achieves 1.5 dB insertion loss and 22 dB isolation. The low insertion loss and high isolation shows that the circuit performance is improved along with the reduction of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Although the conventional series‐shunt switch topology has good isolation and low insertion loss, it suffers from the high insertion loss and poor isolation at the very high frequency more than 20 GHz because of the parasitic capacitances and inductances of small series lines . To overcome these problems, several low loss and high isolation topologies combined with shunt FET and quarter‐wave lines have been reported . In this article, the λ /4 double shunt‐FET structure is employed.…”
Section: Rf Front‐end Module Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the conventional series‐shunt switch topology has good isolation and low insertion loss, it suffers from the high insertion loss and poor isolation at the very high frequency more than 20 GHz because of the parasitic capacitances and inductances of small series lines . To overcome these problems, several low loss and high isolation topologies combined with shunt FET and quarter‐wave lines have been reported . In this article, the λ /4 double shunt‐FET structure is employed.…”
Section: Rf Front‐end Module Designmentioning
confidence: 99%
“…6 To overcome these problems, several low loss and high isolation topologies combined with shunt FET and quarter-wave lines have been reported. 7,8 In this article, the λ/4 double shunt-FET structure is employed. Since it has no series FET, low insertion loss is possible and high isolation is also achievable by optimizing the shunt branch design parameters of FET and parallel resonant lines.…”
Section: Rf Front-end Module Designmentioning
confidence: 99%
“…Filter-integrated switch (FIS) as depicted in Figure 1 is another integrated/multifunction device. From the year 2006 onwards, numerous studies have reported filter-integrated double pole double throw (DPDT) switch [5], single pole single throw (SPST) switch [6][7][8], and SPDT switch [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. In order to produce FISs and integrate BPF with SPDT switch in one device, several techniques have been used, such as dielectric resonators (DRs) [15], LC resonators [11], substrate integrated suspended line (SISL) [30], and common shorted stepped-impedance resonator (CSSIR) [25].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the employment of impedance transformer, the circuit size is large for low frequency applications. To reduce the circuit size, capacitively loaded transmission line resonator can be adopted as in [3]. A bandpass switchplexer based on the direct connection of two switchable parallel-coupled BPF is proposed in [4], but the circuit size is still large.…”
Section: Introductionmentioning
confidence: 99%